1978
DOI: 10.1038/bjc.1978.26
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modifications of the protein of carcinoembryonic antigen: associated changes in immunological activity and conformation

Abstract: Chemical substitution of the exposed residues of tryptophan, tyrosine, histidine and arginine in carcinoembryonic antigen (CEA), using appropriately selective reagents, caused no significant change in the capacity of the antigen to bind to anti-CEA serum. However, treatments of CEA with 2-hydroxy-5-nitrobenzyl bromide and tetranitromethane, both in the presence of guanidine HCl, caused a large reduction in binding capacity. Measurement of the circular dichroism spectra of all of the products showed that retent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…[2,3,4].) Circular dichroism studies of CEA showed that 80% of the molecule is made up of 13 structure and [5 turn, with the other 20% in random coil conformation [20]. Two of them, TM2 and TM4, are similar to NCA, while TM1 and TM3 contain the first disulphide bridge domain plus part of the second from CEA.…”
Section: The Structure Of Ceamentioning
confidence: 99%
“…[2,3,4].) Circular dichroism studies of CEA showed that 80% of the molecule is made up of 13 structure and [5 turn, with the other 20% in random coil conformation [20]. Two of them, TM2 and TM4, are similar to NCA, while TM1 and TM3 contain the first disulphide bridge domain plus part of the second from CEA.…”
Section: The Structure Of Ceamentioning
confidence: 99%
“…The CEA used was isolated from hepatic metastases of a human colonic carcinoma and purified to satisfy criteria described by Westwood & Thomas (1975) and Westwood et al (1978). Anti-CEA sera were raised in a rabbit by the method described by .…”
mentioning
confidence: 99%
“…Earlier [21], the antigenic activity was found to be unchanged following modifica tion of histidine residues accompanied by some alterations of the conformation of anti gen [22], This discrepancy appeared to be connected with the application earlier [21,22] of the antiserum obtained against the protein portion of CEA. This version ap peared likely to be due to the fact that the previous investigations [21,22] were carried out using CEA isolated by extraction with perchloric acid.…”
Section: Discussionmentioning
confidence: 96%
“…This version ap peared likely to be due to the fact that the previous investigations [21,22] were carried out using CEA isolated by extraction with perchloric acid. As was mentioned above, this extraction is accompanied by an altera tion of the conformation of the molecule.…”
Section: Discussionmentioning
confidence: 99%